Клятва майора: роман / А. Тамоников - Тамоников Александр (Спецназ. Воин России, 2012)
Экземпляры: аб. ЦБ (20201207) / Инвентарный номер: 10094 / Цена: / Авт.знак: Т 17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос.Рус)6